2014
DOI: 10.4103/2008-7802.157678
|View full text |Cite
|
Sign up to set email alerts
|

Development of a questionnaire to assess drug abuse among high school students of Isfahan province, Iran: An action research

Abstract: Background:Considering the problem of drug abuse in Iran especially in adolescents and the youth, recent alterations in drug abuse rate and its trend, the necessity to have local information about this problem, applied research has a determining role in management of this problem and making proper decisions. Therefore, the current study was conducted to develop a questionnaire to assess the status of drug abuse among high school students of Isfahan Province, Iran.Methods:This cross-sectional study was conducte… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

0
16
0

Year Published

2018
2018
2024
2024

Publication Types

Select...
8
1

Relationship

0
9

Authors

Journals

citations
Cited by 25 publications
(24 citation statements)
references
References 1 publication
0
16
0
Order By: Relevance
“…It has been reported in previous studies that drug abuse is affected by knowledge and attitude toward drugs. One of such studies is the study of Geramian et al (2014) in Iran, where it was reported that knowledge of substance abuse among youths was able to correct the attitude of youths toward illegal drugs and strengthening their confidence in this regard. They further indicated that to change behaviour, at first knowledge and attitude toward that particular behavior should be corrected.…”
Section: Discussionmentioning
confidence: 99%
“…It has been reported in previous studies that drug abuse is affected by knowledge and attitude toward drugs. One of such studies is the study of Geramian et al (2014) in Iran, where it was reported that knowledge of substance abuse among youths was able to correct the attitude of youths toward illegal drugs and strengthening their confidence in this regard. They further indicated that to change behaviour, at first knowledge and attitude toward that particular behavior should be corrected.…”
Section: Discussionmentioning
confidence: 99%
“…A significant difference was also observed in the present study between high tendency towards addiction and the variables of gender (men), field of study (health), parents' occupation (retired), and history of drug use among family and friends, which is in line with the results obtained in a similar study. 30 Another study showed that the mean score of the tendency towards addiction was significantly higher in the male students and the students who had drug-addicted friends. 31 Students with more aggression tend to focus more on narcotics, and if the environmental situation increases the severity of these features, it will lead to some risky and harmful behaviours such as drug use.…”
Section: Discussionmentioning
confidence: 98%
“…Drug abuse is mainly the result of interaction between person, abused drug, and the environment with changing patterns from time to time [1]. Knowledge and awareness regarding this giant problem and its effects are still less, easy access to drugs at certain places, other factors contribute in substance addiction [2].…”
Section: Introductionmentioning
confidence: 99%